On the use of multi-agent systems for the monitoring of industrial systems, ISSN /e-ISSN 1735-5702 / 1735-5702 - Rezki Nafissa; Kazar Okba; Mouss Leila Hayet; Kahloul Laid (Journal of Industrial Engineering International, 2016)
The objective of the current paper is to present an intelligent system for complex process monitoring, based on artificial intelligence technologies. This system aims to realize with success all the complex process monitoring tasks that are: detection, diagnosis, identification and reconfiguration. For this purpose, the development of a multi-agent system that combines multiple intelligences such as: multivariate control charts, neural networks, Bayesian networks and expert systems has became a necessity. The proposed system is evaluated in the monitoring of the complex process Tennessee Eastman process.